PENGARUH BAURAN PROMOSI TERHADAP MINAT BELI PADA TOKO NAYLA MAJAI SANGATTA UTARA - Ruhani Rasak; Muhammad Nawawi Dg Sibali; Jumri (Tinta Nusantara 2018 Vol.1, 2020)
This study was to determine and analyze whether the influence of the promotion mix has a positive and significant effect on consumer buying interest at the Nayla Sembako Store Majai Sangatta Utara. This study aims to determine and analyze how much influence the consumer's buying interest has at the Nayla Majai store, North Sangatta. The data analysis method used is a quantitative method using multiple linear regression analysis and SPSS version 25. The results of this study indicate that showing new promotions has a positive and significant effect on Consumer Buying Interest at the Nayla Sembako Store, Sangatta Utara. Researchers take research samples directly at the research site and this type of research is an empirical study